The impact of obesity on disease activity and other health outcome measures in rheumatoid arthritis - Ankur Dalal; Rizwan Rajak (Indian Journal of Rheumatology)
Obesity is a common risk factor for noncommunicable diseases such as hypertension and diabetes. It is believed to be a state of low-grade inflammation. Rheumatoid arthritis (RA) is the most prevalent chronic inflammatory arthritis, and obesity is thought to influence its development through adipokines. However, the exact impact of obesity on the disease course of RA is not well understood. This nonsystematic literature review is, therefore, carried out in an effort to understand about how do the obesity affects disease activity (DA) and other health outcome measures in patients with RA. The reviewed evidences suggest that obesity if at all predispose than mostly to the sero-negative RA. Overall, the reviewed data show that obesity may increase DA, but not the radiological joint damage and mortality in patients with RA. However, few evidences also suggest that obesity by itself may actually increase the level of inflammatory markers rather than underlying disease process. These contradictory observations show a definite requirement of further research in this regard and until then weight reduction through reducing fat over lean body mass can be recommended in patients with RA to improve their DA, disability, quality of life, and general cardiovascular status.